An examination of the offences of rape and child defilement in the Nigerian legal system (2016)
Today in Nigeria, the offences of rape and defilement are on the increase. It has become a source of worry to the government, non-governmental organizations and other stakeholders in the country. The effects of these crimes on the victims can have a long lasting effect that transcends from physical to psychological. Sadly, there is also negative attitude of the society towards the victims which makes it difficult for them in most cases to report their occurrences. Due to poor investigation and some defects in the criminal justice system, most of the reported cases, even where prosecuted, usually end up leaving the accused off the hooks. Witnesses are generally reluctant to come to court to testify especially the victims for fear of being discriminated against in the nearest future, hence, perpetrators of these offences quite often than not go scot free. This paper defines the offences of rape and defilement and examines their elements, such as penetration, consent and corroboration under the Nigerian criminal jurisprudence. It also looks at the effects of the offences on the victims and the society at large. By way of recommendations and conclusion, the paper also suggests pragmatic means to combat these offences and treatment of its victims, drawing on good examples from jurisdictions like United Kingdom and America.